Energy Monitoring of Innovative Energy Technologies of Plant Raw Material Processing - Burdo O.G.; Gavrilov A.V.; Kashkano M.V.; Levtrynskaya Y.O.; Sirotyuk I.V.; Pylypenko E.A.; Terziev S.G. (Problems of the Regional Energetics, 2019)
The analysis of scientific works shows that the development of technology is ahead of the level of development of energy management. There are no clear comparisons of the energy efficiency of electrical technologies and heat technologies. Objective indicators of energy efficiency in various technologies of dehydration of raw materials not developed yet. In that article assumed that objective results for comparing energy efficiency in the processing of raw materials is ob-tained by the basis of system analysis of the entire energy conversion chain from fuel to fin-ished product. The purpose of the work is experimentally proving the objectivity of this hypoth-esis. To achieve this goal, it is proposing to use the indicator of the energy share of fuel in the finished product and the amount of moisture removed when burning 1 kg of fuel, which does not depend on fluctuations in energy prices, which can vary and differ for different countries. The most important result of the work is the comparison of these parameters with the data for innovative equipment samples developed by the authors. The significance of the results ob-tained is that the evaporating devices developed by the authors are not inferior in efficiency to traditional ones, and make it possible to obtain concentrates up to 90 ° brix. Thus, for fuels with an oil equivalent of 40 MJ per 1 kg, traditional dryers can remove no more than 3 kg of mois-ture, cryoconcentrators – 20 kg.